Edukasi Video Animasi Demam Berdarah Dengue pada Siswa SD Inpres Lae-Lae 2 Kota Makassar - Majid, Abdul; Erika, Kadek Ayu; Hasbiah, Nurhikmawaty; Harisa, Akbar; Yodang, Yodang (Jurnal Abdimas Kesehatan (JAK), 2024)
Dengue Hemorrhagic Fever (DHF) is one of the most serious public health problems in Indonesia. Based on data from the Makassar City Health Office, the number of DHF cases from January to February in 2022, recorded as many as 95 cases in Makassar City. SD Inpres Lae-Lae 2 Makassar City is one of the schools located in coastal areas that are prone to dengue transmission because there are many puddles and garbage that become breeding grounds for Aedes aegypti and Aedes albopictus mosquitoes. This community service activity aims to provide knowledge and increase students' awareness of dengue hemorrhagic fever and how to prevent it and this activity in line with the Sustainable Development Goals (SDGs) target program, namely to create quality education and realize a healthy and prosperous life. This activity was carried out at SD Inpres Lae-Lae 2 Makassar City on May 20th 2024.From this activity, it was found that students experienced an increase in knowledge from 27.5% to 45%, which was measured using a pre-test and post-test questionnaire. It is hoped that this activity will become a reference for schools as a medium of education and learning for students to be able to continue to make efforts to prevent or develop Dengue Hemorrhagic Fever (DHF) prevention programs in the school environment.